PEMBERDAYAAN MASYARAKAT DESA MELALUI SOSIALISASI AGRIBISNIS AYAM JOPER DI DESA SUNGAI BATU GANTIH KECAMATAN GUNUNG KERINCI KABUPATEN KERINCI PROVINSI JAMBI - Ridho Kurniawan Rusli; Rusfidra Rusfidra; Kusnadidi Subekti; Amri Syahardi; Sosmiarti Sosmiarti; Arfan Hanafi (Jurnal Hilirisasi IPTEKS, 2024)
The empowerment of village communities is within the framework of the Independent Campus Learning Program (MBKM) Building Villages, which is carried out for the people of Sungai Batu Gantih Village, Gunung Kerinci District, Kerinci Regency, Jambi Province. Based on the results of a preliminary survey in Sungai Batu Gantih Village, in general, the village community carries out their livestock business part-time, with food crop farming activities as the main business. The knowledge of the people of Sungai Batu Gantih Village regarding the cultivation of free-range chickens is still low. Chicken rearing is carried out extensively, relying on household leftovers as feed, resulting in low productivity and a limited population. So, this activity aims to improve the abilities and skills of village communities in raising chickens through socializing the joper chicken so that they can increase productivity and increase people's income in Sungai Batu Gantih Village. Joper chickens are the result of crossing male Joper chickens and female purebred chickens with quite high egg production, and the eggs and meat have a distinctive taste. This activity will be carried out in September–December 2022. The method of activity carried out is participatory community empowerment, which includes counseling, field practice, and mentoring. The implementation of empowerment activities went well and received a positive response from the village community. This was shown by the percentage of Joper chickens that lived to 4 weeks of age, reaching 90% with a body weight ranging from 230 to 290 g/head.